Plicní a mimoplicní mykobakteriózy - Bártů, V (Epidemiologie, mikrobiologie, imunologie, 1998)
Pulmonary and extrapulmonary mycobacterioses are diseases with a less frequent incidence. They affect in particular subjects in an immunodeficient state and with chronic pulmonary disease. The diagnosis is based on the clinical picture, pathological X-ray picture and repeated positivity of the examined biological material with subsequent identification of the mycobacterial strain. These microorganisms are found in nature, infection occurs most frequently by inhalation and interpersonal transmission was never proved so far. Extrapulmonary manifestations are associated with lymphadenitis, affections of the skin and soft tissues. In therapy which extends over several months a combination of antituberculotics and antibiotics is used which are effective against the particular mycobacterium. In indicated cases a surgical approach should be used. The author presents a list of mycobacteria types of diseases they produce, as well as an account on the diagnostic and therapeutic approach.
Keywords: Mycobacterium Infections, Nontuberculous; Tuberculosis, Pulmonary; atypické mykobakteriální infekce; lidé; plicní tuberkulóza; Humans